HPP improves the emulsion properties of reduced fat and salt meat batters by promoting the adsorption of proteins at fat droplets/water interface. (February 2021) - Yang, Hui-Juan; Han, Min-Yi; Wang, Hai-feng; Cao, Guang-tian; Tao, Fei; Xu, Xing-Lian; Zhou, Guang-Hong; Shen, Qing
Abstract: The aim of this study was to explore whether the state of the formation of interfacial protein film (IPF) could be utilized to increase the emulsion ability modified by high pressure processing (HPP). The meat emulsion was obtained from the meat batters with reduced fat and reduced salt (RFRS). The results revealed the highest stability and activity of meat emulsion were obtained as 68.12% and 76.89% at 200 MPa, respectively, and the minimized diameter of emulsion particles was D 3, 2 2.29 μm. Besides, after obtaining the interfacial proteins (IPs) and the fat droplets individually, the diameter of fat droplets and proportion of ionic bonds first decreased then rose along with increasing pressure, and the lowest values were exhibited at 200 MPa. In contrast, the adsorbed IPs content (0.657 mg/m 2 ), zeta potential (−0.27), hydrophobic interactions (63.57%), hydrogen bonds (83.29%), and disulfide bonds (75.69%) presented the opposite trends, with the highest value also exhibited at 200 MPa. In conclusion, 200 MPa helped proteins adsorbed at the interface, corresponding with the unfolding conformational rearrangement and reorientation of IPs at the interface with the dispersed fat droplets. Highlights: HPTT improved the tenderness of RFRS meat batters. HPTT modified the water distribution characteristics. The free water shifting to immobilized water and bound water was conducted by HPTT. The protein-protein interaction could be qualitatively evaluated by CLSM.